Vegetarian diet is inversely associated with prevalence of depression in middle-older aged South Asians in the United States. Issue 4 (19th May 2021) - Jin, Yichen; Kandula, Namratha R.; Kanaya, Alka M.; Talegawkar, Sameera A.
ABSTRACT: Objective: To investigate associations between a vegetarian diet and depression among South Asians in the United States. Design: Data from 892 South Asians (age range 40–83 y, 47% women) enrolled in the Mediators of Atherosclerosis in South Asians Living in America (MASALA) study were included. A vegetarian diet was defined as no intake of meat, poultry or fish in the previous year as reported on a validated food frequency questionnaire. Depressive symptomology was assessed using the Center for Epidemiologic Studies-Depression Scale (CES-D) and depression was classified as CES-D score ≥16. Multivariable logistic regression was used and covariates included age, sex, study site, education, smoking, body mass index, acculturation, intentional exercise, alcohol and energy intake, and antidepressant medication use. Results: Our study demonstrated 43% lower odds of depression among vegetarians ( p  = 0.023). Conclusions: Vegetarian diet was found to be inversely associated with the prevalence of depression. Longitudinal examinations confirming these findings are needed.